Effect of prolonged head-down bed rest on complex cardiovascular dynamics - Fortrat, Jacques-Olivier; Sigaudo, Dominique; Hughson, Richard L; Maillet, Alain; Yamamoto, Yoshiharu; Gharib, Claude (Autonomic Neuroscience, 2001)
We postulated that a change in complex dynamics of the cardiovascular system could be involved in the orthostatic intolerance observed after simulated weightlessness. Supine recordings of 1024 consecutive pulse intervals and systolic blood pressures were obtained on 7 subjects adapted to a 42 day head-down bed rest (day 22 and 42) but also before and 6 days after head-down bed rest (−6°). Coarse graining spectral analysis was used to extract the non-harmonic (fractal) component from each time series. The power spectral densities of this fractal component are inversely proportional to their frequency (1/f β). We fitted an inverse power law estimate to the fractal component to determine the spectral exponent β. The complex dynamics of blood pressure and heart rate variability were also analyzed by correlation dimension and non-linear prediction. Bed rest induced orthostatic intolerance in 4 subjects. There was a significant increase in the spectral exponent β of RR-interval variability during and after head-down bed rest (before: 1.039±0.090; during: 1.552±0.080 and 1.547±0.100; after: 1.428±0.040). Analysis of the blood pressure dynamics indicated lower correlation dimensions during head-down bed rest and higher coefficients of predictability after head-down bed rest. Complexity alterations of RR-interval and blood pressure variability were not linked with one another during head-down bed rest. These alterations seemed to be correlated with the orthostatic intolerance observed after bed rest. These results suggest a change of the integration level of cardiovascular autonomic regulation.